Detection of a Variant Metallo-β-Lactamase, IMP-10, from Two Unrelated Strains of Pseudomonas aeruginosa and an Alcaligenes xylosoxidans Strain - Iyobe, Shizuko (American Society for Microbiology, 2002)
The gene bla(IMP-10) of a variant metallo-β-lactamase, IMP-10, had a single base replacement of G by T at nucleotide 145, which led to an amino acid alteration of Val49 to Phe compared to the IMP-1 enzyme, indicating that IMP-10 was a point mutation derivative of IMP-1. Highly purified enzymes revealed that IMP-10 was different from IMP-1 in its extremely low hydrolyzing activities for penicillins, such as benzylpenicillin, ampicillin, and piperacillin.